Accelerate the Transition to International Financial Reporting Standards (Eurasian Scientific Herald, 2023)
The article contains opinions on the nature of international financial reporting standards (IFRS), ongoing work to ensure the implementation of PD-4611, and modern methods of teaching international financial reporting standards.